The role of macrophage-derived TGF-β1 on SiO2-induced pulmonary fibrosis: A review. (April 2021) - Zhang, Zhao-qiang; Tian, Hai-tao; Liu, Hu; Xie, Ruining
Silicosis is an occupational fibrotic lung disease caused by inhaling large amounts of crystalline silica dust. Transforming growth factor-β1 (TGF-β1), which is secreted from macrophages, has an important role in the development of this disease. Macrophages can recognize and capture silicon dust, undergo M2 polarization, synthesize TGF-β1 precursors, and secrete them out of the cell where they are activated. Activated TGF-β1 induces cells from different sources, transforming them into myofibroblasts through autocrine and paracrine mechanisms, ultimately causing silicosis. These processes involve complex molecular events, which are not yet fully understood. This systematic summary may further elucidate the location and development of pulmonary fibrosis in the formation of silicosis. In this review, we discussed the proposed cellular and molecular mechanisms of production, secretion, activation of TGF-β1, as well as the mechanisms through which TGF-β1 induces cells from three different sources into myofibroblasts during the pathogenesis of silicosis. This study furthers the medical understanding of the pathogenesis and theoretical basis for diagnosing silicosis, thereby promoting silicosis prevention and treatment.